2006
DOI: 10.1191/0961203306lu2292oa
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of isolated severe immune hemolytic anaemia associated with systemic lupus erythematosus: 26 cases

Abstract: The aim of this study was to evaluate the response to treatment and the long-term outcome in a cohort of patients in whom severe autoimmune hemolytic anaemia (AHA) was the leading manifestation of systemic lupus erythematosus (SLE). Twenty-six women with severe isolated AHA were included. Corticosteroids were used as the initial treatment for all patients in our study. An initial response was obtained in all but one patient (96%). The overall recurrence rate was three per 100 person-years, with an expected rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 23 publications
0
33
0
5
Order By: Relevance
“…On a maintenance treatment of 5 to 20 mg of PDN (in some patients with additional azathioprine or cyclophosphamide) the recurrence rate was low (3-4/100 patient-years). 81 The same second-line treatments as in primary AIHA have been effective in some cases. 81 Rituximab has been effective in single cases, but there is a concern of an increased risk of PML in this particular disease.…”
Section: Treatment Of Secondary Aihamentioning
confidence: 99%
See 1 more Smart Citation
“…On a maintenance treatment of 5 to 20 mg of PDN (in some patients with additional azathioprine or cyclophosphamide) the recurrence rate was low (3-4/100 patient-years). 81 The same second-line treatments as in primary AIHA have been effective in some cases. 81 Rituximab has been effective in single cases, but there is a concern of an increased risk of PML in this particular disease.…”
Section: Treatment Of Secondary Aihamentioning
confidence: 99%
“…81 The same second-line treatments as in primary AIHA have been effective in some cases. 81 Rituximab has been effective in single cases, but there is a concern of an increased risk of PML in this particular disease. Splenectomy seems to have only a low long-term efficacy.…”
Section: Treatment Of Secondary Aihamentioning
confidence: 99%
“…AIHA is often associated with thrombocytopenia, lupus nephritis and CNS activity. To address the natural history and treatment response in AIHA among SLE patients, Gomrad et al [8] studied 26 patients with severe isolated AIHA. The authors observed that AIHA is a serious complication of SLE, requiring urgent and appropriate management.…”
Section: Discussionmentioning
confidence: 99%
“…In relapsed or refractory cases, immunosuppressive agents, danazol or rituximab can be tried although there is not a consensus for the treatment of relapsed refractory cases. Although rituximab is a promising agent as a second line treatment in SLE patients with AIHA, the safety and efficacy should be documented with prospective randomized studies [22][23][24].…”
Section: Treatment Strategies General Aspects On the Treatment Of Secmentioning
confidence: 99%